MAKNA DENOTASI DAN MAKNA KONOTASI PADA FILM 3 IDIOTS KARYA RAJKUMAR HIRANI - Sumendap, Inggrid Nathalia; Rambing, Rosalina; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Inggrid Nathalia SumendapÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dra. Rosalina R. Rambing, DEAÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Garryn Ch. Ranuntu, S.Pd, M.HumÂ Â Â Â This research entitled is â€œSemiotic Analysis in The Movie 3 Idiotsâ€. The objectives of this research are to indentify, classify, and analyze the denotative and connotative meanings in the 3 Idiots film. In this study, the authors used the theory of Barthes (1977) with the concept of denotation and connotation. Denotation is what we think of as a fixed literal and has a dictionary meaning in a word. Meanwhile, connotation is a change in the meaning of a word. In theory, all cultural objects can be processed textually. Thus, semiotics can examine various kinds of texts, one of which is film.. The results showed, there are 25 denotational meanings that explain the literal meaning of words and 25 connotative meanings that explain the expression or additional meaning of a word.Keywords : Semiotic, Denotation, Connotation, Film